Benefits and limitations of local food economies to promote sustainability : a Stellenbosch case study - Schulschenk, Jess (Stellenbosch : University of Stellenbosch, 2010)
Thesis ((MPhil (Sustainable Development Management and Planning))--University of Stellenbosch, 2010.